Leaving No One Behind?: Informal Economies, Economic Inclusion and Islamic Extremism in Nigeria. (August 2015) - Meagher, Kate; Gore, Charles
Abstract This article examines how the Post‐2015 commitment to economic inclusion affects informal economic actors in developing countries. It highlights the selective dynamics of inclusive market models that generate new processes of exclusion in which the most vulnerable continue to be left behind. The case of Nigeria reveals how inclusive market initiatives reinforce parallel processes of informalization, poverty and Islamic extremism in the north of the country. Fieldwork in northern Nigeria shows that inclusive initiatives are intensifying competitive struggles within the informal economy in which stronger actors are crowding out poorer, less educated and migrant actors, exacerbating disaffection and vulnerability to radicalization. Copyright © 2015 John Wiley & Sons, Ltd.